Hubungan Pengetahuan Dan Pola Menstruasi Dengan Kejadian Anemia Pada Remaja Putri Di SMA Negeri 1 Perhentia Raja Tahun 2022 - Yanis, Heri; Apriyanti, Fitri; Hastuty, Milda (Evidence Midwifery Journal, 2023)
Anemia in adolescents is a health problem where the hemoglobin (HB) level in the blood is lower than the normal value for the age group and gender, in female adolescents the normal hemoglobin (HB) is 12 gr/dl and in males 13 gr/dl. The aim of the research is to analyze the relationship between knowledge and menstrual patterns and the incidence of anemia in young women at SMA Negeri 1 Perhantian Raja, Kampar Regency in 2023. The type of research is quantitative analytical research with a cross sectional design. The research was conducted on June 16-June 19 2023 with a sample of 205 young women at SMA Negeri 1 Perhentian Raja, Kampar Regency, using total sampling data collection techniques. Data collection uses a questionnaire. The data analysis used was univariate and bivariate analysis with the Chi Square test. The results of the final assignment report showed that there was a relationship between knowledge and menstrual patterns and the incidence of anemia in young women at SMA Negeri 1 Perhentian Raja, Kampar Regency (p value = 0.010) knowledge, (p value = 0.000). The conclusion is that there is a significant relationship between knowledge and menstrual patterns and the incidence of anemia in young women at SMA Negeri 1 Perhentian Raja, Kampar Regency. It is hoped that the SMAN 1 Perhentian Raja school can collaborate with the Health Service through the Community Health Center to further improve UKS (Health and School Business) and PIKR (Youth Information and Counseling Center). As well as reviving the PKPR (Youth Care Health Services) program with more frequent intensity